Xylooligosaccharide supplementation alters gut bacteria in both healthy and prediabetic adults: a pilot study - Yang, Jieping; Summanen, Paula H.; Henning, Susanne M.; Hsu, Mark; Lam, Hei Man; Huang, Jianjun; Tseng, Chi-Hong; Dowd, Scot E.; Finegold, Sydney M.; Heber, David; Li, Zhaoping (Frontiers in Physiology, 2015)
Background: It has been suggested that gut microbiota is altered in Type 2 Diabetes Mellitus (T2DM) patients. Objective: This study was to evaluate the effect of the prebiotic xylooligosaccharide (XOS) on the gut microbiota in both healthy and prediabetic (Pre-DM) subjects, as well as impaired glucose tolerance (IGT) in Pre-DM. Subjects/Methods: Pre-DM (n = 13) or healthy (n = 16) subjects were randomized to receive 2 g / day XOS or placebo for 8-weeks. In Pre-DM subjects, body composition and oral glucose tolerance test (OGTT) was done at baseline and week 8. Stool from Pre-DM and healthy subjects at baseline and week 8 was analyzed for gut microbiota characterization using Illumina MiSeq sequencing. Results: We identified 40 Pre-DM associated bacterial taxa. Among them, the abundance of the genera Enterorhabdus, Howardella and Slackia was higher in Pre-DM. XOS significantly decreased or reversed the increase in abundance of Howardella, Enterorhabdus and Slackia observed in healthy or Pre-DM subjects. Abundance of the species Blautia hydrogenotrophica was lower in pre-DM subjects, while XOS increased its abundance. In Pre-DM, XOS showed a tendency to reduce OGTT 2-h insulin levels (P = 0.13), but had no effect on body composition, HOMA-IR, serum glucose, triglyceride, satiety hormones and TNFα. Conclusion: This is the first clinical observation of modifications of the gut microbiota by XOS in both healthy and Pre-DM subjects in a pilot study. Prebiotic XOS may be beneficial in reversing changes in the gut microbiota during the development of diabetes.